Maus tratos, comportamento externalizante e autoestima: um estudo comparativo - Melo, Débora Cristina Fava (2013)
Maltreatment experienced by the child are considered harmful to child development and a risk factor for the development of behavior problems in adolescence. Have been associated with externalizing behavior and low self-esteem, which can negatively influence the psychological development of the individual and social behavior. This dissertation stems from a larger project developed at the Graduate Program in Psychology, Faculty of Psychology / PUCRS from the National Postdoctoral (PNPD), entitled "Exposure to child maltreatment and its relationship with cognition, psychological adjustment and the occurrence of psychopathology in adolescents, adults and the elderly". The objective of original project (PNPD) is to investigate the effects of exposure to childhood maltreatment on cognition and expression of psychopathology in adolescence, adulthood and old age. This dissertation is presented in two parts, the first study "Relationship between abuse, self-esteem and externalizing behavior: a comparative study", and study 2 "Risk factors for the development of externalizing behavior in adolescents". The goal of Study 1 was to investigate the relationship between maltreatment, externalizing behavior and self-steem, while the second study sought to evaluate the predictive value of self-esteem and abuse in externalizing behavior. Both studies deal with a cross transveral methodology. The instruments used were the Childhood Trauma Questionnaire, Youth Self-Report, Child Depression Inventory, Rosenberg Self-Esteem Scale, and a data sheet Sociodemographic and Economic Classification Criterion Brazil. The study included 84 adolescents from public schools. Results from a comparative analysis showed that adolescents who experienced childhood maltreatment had greater symptoms of externalizing behavior and poor self-esteem than those who did not undergo this kind of experience. Moreover, a correlation analysis found that outsourcing and maltreatment were positively correlated with each other as well as with symptoms of anxiety, withdrawal and depression and other behavior problems. Self-esteem was negatively correlated with maltreatment and behavior problems. Through multiple linear regression (stepwise method), results showed that symptoms of anxiety and depression, coupled with a history of physical abuse, 22% of the explained variance of externalizing behavior. Self-esteem got low performance, only 1% for the prediction of externalizing individual variables in the analysis (method enter). The results of these studies may help professionals to think and act on the importance of promoting factors that prevent children suffering from abuse, as well as outsourcing and low self-esteem, avoiding problems in psychological and behavioral development. Knowing the predictors of externalizing behavior may help in developing interventions and prevention strategies.